2021
DOI: 10.3389/fnhum.2021.637071
|View full text |Cite
|
Sign up to set email alerts
|

Functional Network Alterations as Markers for Predicting the Treatment Outcome of Cathodal Transcranial Direct Current Stimulation in Focal Epilepsy

Abstract: Background and PurposeTranscranial direct current stimulation (tDCS) is an emerging non-invasive neuromodulation technique for focal epilepsy. Because epilepsy is a disease affecting the brain network, our study was aimed to evaluate and predict the treatment outcome of cathodal tDCS (ctDCS) by analyzing the ctDCS-induced functional network alterations.MethodsEither the active 5-day, −1.0 mA, 20-min ctDCS or sham ctDCS targeting at the most active interictal epileptiform discharge regions was applied to 27 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Conversely, for the latest, we observed a tendency to an increase of Fc at the end of the study. In line with these findings, a recent study has used Fc with fMRI as a quantitative measure of tDCS effects on brain activity in patients with epilepsy (Hao et al, 2021). This study showed that the response to the cathodal tDCS was linked to functional network alterations with a decreasing Fc in patients responding to the active cathodal tDCS.…”
Section: Functional Connectivitymentioning
confidence: 57%
“…Conversely, for the latest, we observed a tendency to an increase of Fc at the end of the study. In line with these findings, a recent study has used Fc with fMRI as a quantitative measure of tDCS effects on brain activity in patients with epilepsy (Hao et al, 2021). This study showed that the response to the cathodal tDCS was linked to functional network alterations with a decreasing Fc in patients responding to the active cathodal tDCS.…”
Section: Functional Connectivitymentioning
confidence: 57%
“…They considered that tDCS induced a cumulative clinical benefit with reduction in SF in epileptic patients, associated with a decrease in synchronization. A more recent study aimed to evaluate and predict the potential clinical efficacy of cathodal tDCS by analyzing the induced functional network alterations (Hao et al, 2021 ). The 27 epileptic patients were separated in two groups of stimulation: sham group and active cathodal tDCS group with 20-min stimulation at −1 mA, for 5 consecutive days, targeting the regions with higher IEDs rate.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies focusing on functional brain network changes have highlighted interesting results between the response to tDCS therapy and functional disturbances in global brain networks (Lin et al, 2018 ; Tecchio et al, 2018 ; Daoud et al, 2022 ). Measuring FC changes may thus be a possible predictor of the tES clinical efficacy in epileptic patients (Hao et al, 2021 ). However, measuring changes in functional connectivity after tDCS in epilepsy has some limitations.…”
Section: Discussionmentioning
confidence: 99%